2020
DOI: 10.1007/s00167-020-06192-1
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Bankart repair with all-suture anchors does not cause important glenoid bone osteolysis: a volumetric CT study of 143 anchors

Abstract: Purpose To evaluate with computed tomography (CT) the incidence of anchor-related osteolysis after implantation of two types of all-suture anchors for the management of labral lesions in shoulder instability. Methods Single-cohort, observational study with 12-month follow-up. Thirty-three participants (27 males/6 females; age 38.3 years [SD 11.3]) with anterior labral lesions in which 143 all-suture anchors (71 Iconix 1.4 mm and 72 Sutureix 1.7 mm) were implanted were evaluated with a CT performed a mean of 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…All measurements were made twice and the mean was used for further calculations. This measurement method has showed a high intraobserver and interobserver reproducibility (Intraclass Correlation Coeicient > 0.9) [24].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…All measurements were made twice and the mean was used for further calculations. This measurement method has showed a high intraobserver and interobserver reproducibility (Intraclass Correlation Coeicient > 0.9) [24].…”
Section: Discussionmentioning
confidence: 93%
“…All patients received oral and written information about the study and written consent for participation and follow-up for 12 months was obtained. This is a post hoc analysis of the images available from a previous study designed to assess the incidence of glenoid osteolysis after implantation of all-suture anchors for the management of labral lesions [24]. A total of 33 subjects in which an arthroscopic Bankart repair performed with allsuture anchors were included in the initial study; these subjects were evaluated prospectively with a computed tomography (CT) at 1-year follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyst formation and statistically significant increased tunnel expansion was seen in postoperative CT imaging, but it did not influence clinical outcomes. 39,[43][44][45] MRI studies showed various bone reactions, such as tunnel widening, cyst formation and rims of fluid around the anchors, but these reactions were considered as not statistically significant. 36,41 However, one MRI study executed by Ro et al 40 did show a peri-anchor cystic bone reaction being associated with a higher rate of rotator cuff retears.…”
Section: Discussionmentioning
confidence: 99%
“…The radiographs were evaluated by two independent researchers, with a detailed review of the presence of bony abnormalities at the site of the anchor. 45 ASAs could not be evaluated on postoperative imaging, mostly due to metallic artifacts of osteosynthesis material, and were not included in the final analysis. The diameter of the anchor drill hole was measured and the morphology of the drill hole was documented.…”
Section: Methodsmentioning
confidence: 99%